'A threat to us': The interplay of insecurity and enmity narratives in left-wing populism. (August 2022) - Bonansinga, Donatella
Left-wing populists are understudied in populism research and little is known on how enmity and insecurity narratives interplay in their rhetoric. Using a narrative framework to capture insecurity in the 'enemification' of elites, this article examines left-populist Jean-Luc Mélenchon and La France Insoumise. The analysis reveals a multifaceted construction of national, supranational and international elites as sources of insecurity, based on (a) the threats they pose, (b) the uncertainty they generate and (c) their failure to protect citizens. The article makes two contributions to the populism and International Relations literatures. First, it provides empirical evidence to contest the hypothesis that left populism promotes pluralist agonism rather than antagonism. Second, it shows how populists across the spectrum can use insecurity-centred narratives to delegitimise elites from speaking security and promote an agenda centred on popular sovereignty.